REVIEW: Noted: Pacific climate change doco lacks ‘media impact’ - Taberannang Korauaba (Asia Pacific Network, 2013)
"On the night the The Hungry Tide was screened on Māori Television in New Zealand, our family was having a farewell party for our relatives returning to Kiribati the next day. We sat cross-legged on a mat in a circle while women prepared meals for everyone... of course our family members were going to watch the 'movie' rather than a documentary. They were going to re-connect their memories of Kiribati through this film. Not suprisingly, climate change and sea level rise are already a disaster on the minds of these people."